A minimum-time obstacle-avoidance path planning algorithm for unmanned aerial vehicles - De Marinis, Arturo; Iavernaro, Felice; Mazzia, Francesca (Numerical algorithms, 2022)
In this article, we present a new strategy to determine an unmanned aerial vehicle trajectory that minimizes its flight time in presence of avoidance areas and obstacles. The method combines classical results from optimal control theory, i.e. the Euler-Lagrange Theorem and the Pontryagin Minimum Principle, with a continuation technique that dynamically adapts the solution curve to the presence of obstacles. We initially consider the two-dimensional path planning problem and then move to the three-dimensional one, and include numerical illustrations for both cases to show the efficiency of our approach.